Vocational Skills Education at Semarang State Special School - Dewi Kurniati; Munawir Yusuf; Subagya Subagya; Joko Yuwono (International Inclusion Development and Cooperation, 2023)
Every child must have life skills from the results of the educational process, especially mentally retarded children. Vocational skills education is one of the learning models used in special schools to train life skills in mentally retarded children. The purpose of this research is to analyze and describe vocational skills education held at Semarang State Special School. The research method uses descriptive qualitative. The subjects of this study were the principal and teachers of Semarang State Special School. The results of the study show that the implementation of vocational education is in accordance with the interests of the talents possessed by students. Vocational education is carried out with careful and systematic planning in achieving the goals of the education. Students must have personal, social, and economic independence. Vocational education is carried out by teachers who already have vocational skills so that the material provided is in accordance with the teacher's expertise. The school provides several types of skills, including ceramics, wood crafts, batik, beauty, fashion, cooking, agriculture, automotive, IT, and housekeeping.